Servicio al cliente en la Distribuidora de plásticos "TODO WOW" de la Ciudad de Babahoyo, periodo 2024. - De Lucas Cruz, Luis Gabriel (2025)
The research was carried out at the plastics distributor "TODO WOW", which is a private company, located on the streets: Martin Icaza between June 5 and August 10, in the city of Babahoyo, Babahoyo canton, Los Ríos Province. Its main activity is the distribution and marketing of plastic products such as: plates, covers, glasses, bags, spoons, paper bags and napkins, it began its commercial operations on June 20, 2019, having as clients a diversity of businesses such as: Restaurants, fruit shops with cream and others. Likewise, there are also clients who are natural persons and who purchase the products for the different activities they carry out. Its objective was to evaluate the quality of customer service at the Plastics Distributor during the period 2024, to identify critical areas and recommend strategies that optimize the customer experience. The method used in this case study was the inductive method applied to analyze data from surveys and interviews, looking for patterns that reveal how customer service has been affected at the Plastics Distributor. The results showed that the company has had a customer service process characterized by promptness in service, personnel willing to resolve concerns of its customers, but with a customer portfolio where 40% have difficulty obtaining detailed and clear information about prices and characteristics of the products. It was evident that in general 86% of customers have a positive level of satisfaction about their experience in relation to the service received at the Plastics Distributor, this being a competitive advantage, but requiring a thorough analysis of its critical points to improve.